1990
DOI: 10.1093/clinchem/36.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Basement membrane-related and type III procollagen-related antigens in serum of patients with chronic viral liver disease

Abstract: To assess the significance of serum basement membrane- and type III procollagen-related antigens in reflecting the degree of liver fibrosis, we measured radioimmunologically the concentrations of 7S collagen, laminin fragment P1, and the aminoterminal propeptide of type III procollagen (P-III-P) in serum from 48 patients with chronic viral liver disease: chronic persistent hepatitis (9), chronic active hepatitis (13), chronic active hepatitis with lobular disorganization (17), and liver cirrhosis (9). Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In our series the highest values of laminin were observed in cirrhotic patients, as in previous studies (39,40). During interferon therapy we noted a decrease in the mean concentrations of laminin in patients who responded, although this reduction was not significant.…”
Section: Discussionsupporting
confidence: 86%
“…In our series the highest values of laminin were observed in cirrhotic patients, as in previous studies (39,40). During interferon therapy we noted a decrease in the mean concentrations of laminin in patients who responded, although this reduction was not significant.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, the presence of collagen fragments in the serum has been used as a diagnostic marker for cirrhosis. For example, the presence of fragments of type IV and type III collagen (Misaki et al, 1990), fragment of type IV collagen (Obata et al, 1989) and the fragments of type IV collagen and 7S do- Fig. 4.…”
Section: Discussionmentioning
confidence: 98%
“…Various serum markers that can be used to evaluate the progression of hepatic fibrosis have also been reported (Tanikawa, 1994;Tsutsumi et al, 1996). Pro-type III collagen and the triplehelical domain and 7S domain of type IV collagen are used as the serum markers for cirrhosis (Obata et al, 1989;Misaki et al, 1990;Murawaki et al, 1996). In cirrhosis, several types of collagen increase at various ratios (Rojkind and Ponce-Noyola, 1982;Murata et al, 1984).…”
mentioning
confidence: 99%
“…The fibrillar collagens, types I and III, become the main ECM proteins produced by hepatic stellate cell (HSC) that has been activated by pathogenic changes in the hepatic cells and tissues. Several reports have shown that expression of collagen type III alpha 1 ( COL3A1 ) is increased in viral (HBV and hepatitis C virus) or alcohol related‐liver diseases including chronic liver diseases (7), liver fibrosis (8, 9), liver cirrhosis (CIR) (10, 11), and HCC (12). Moreover, synthetic analogues of Arg‐Gly‐Asp (RGD) have been shown to inhibit integrin‐mediated cell function between T lymphocytes and ECM in acute liver injury (13).…”
Section: Introductionmentioning
confidence: 99%